Interrelations between income inequality and sustainable economic growth: Contradictions of empirical research and new results - Mikhail Dorofeev (Economies, 2022)
The idea that high levels of economic inequality negatively affect the rate and sustainability of economic growth is quite popular in the scientific literature. Therefore, it is usually proposed to take some regulative measures to reduce economic inequality in order to boost economic growth. Should the thesis be considered as a populist slogan or a scientifically proven fact? This article analyzes the results of 22 empirical studies on the relationship between economic inequality and economic growth conducted during the period of 1917-2018. We used meta-analysis to examine and systematize the results of previous empirical studies. The literature review and the analysis of the results from previous studies mainly indicate a negative relationship between economic inequality and economic growth (59% of the previous empirical research). The research gap is that on average these studies are rather controversial to each other and we cannot say that we understand these relationships correctly. To answer the questions concerning the interrelations between income inequality and sustainable economic growth, we made our own empirical research. To do this we used a qualitative pairwise correlation comparison method and analyzed panel data of 39 countries for the period of 1980-2019. The correlation between income inequality and sustainable economic growth was evaluated basing on the Gini index (GI) and Gross Domestic Product (GDP). Our calculations and analysis show that on average, in approximately 57.8% of moments in the period between 1980-2018, this correlation was positive in our sample of countries. The novelty of our study is that we show in detail how income inequality and economic growth are interconnected for each particular country and on average for the whole sample of countries. In addition, we used the inequality transparency index to adjust our calculations for data quality. Three hypotheses were tested in the study. Only one of them was confirmed by our research. The level of income inequality determines the direction of its impact on economic growth. An increase in income inequality in countries with low levels of inequality in most cases boosts economic growth and vice versa. Additionally, we received partial confirmation of our other hypothesis and found out that the correlation between economic growth and income inequality is definitely more negative for countries with low income and more positive in countries with high income per capita.
Keywords: 330; economic growth; economic inequality; GDP; Gini index; government financial regulation; income inequality; poverty; progressive taxes; sustainable growth